Terrorist financing and money laundering - Драний, Валерій Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The objecte of this work is to identify the financing methods used by terrorists and how they differ from those used by other criminal groups. The efforts also sought to determine whether distinctions between legaland illegal funding sources affect the ability of countries to use anti-money laundering measures in detecting, investigating and prosecuting terrorists related financial activity.